Brisket (high altitude) disease in Ethiopia cattle: Cases investigated - Njau, B.C.; Kasali, O.B. (1989)
Reports results of an investigation on Brisket (high mountain) disease in calves born at the ILCA Debre Berhan Station. Includes data on findings at necropsy and cases of pneumonia that died.